Kemampuan Berpikir Kreatif Siswa dalam Memecahkan Masalah HOTS Ditinjau dari Gaya Kognitif - Siti Amina; Enny Listiawati; Moh Affaf (Universitas Muria Kudus, 2020)
The purpose of this study was to describe students' creative thinking skills in solving HOTS problems in terms of cognitive style. The subjects in this study were 2 female students of grade VII SMP consisting of 1 student with a field-independent cognitive style and 1 student with a field-dependent cognitive style. The research instrument consisted of GEFT test questions to determine students' cognitive style, HOTS math questions in the form of description questions on triangular flat shapes, and interview guidelines. The data collection technique used technical tests followed by semi-structured interviews to confirm students' creative thinking abilities. Test data credibility by triangulation, while the technical analysis of data through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the subject with the field-independent cognitive style met the indicators of creative thinking fluency and flexibility, and was at the level of creative thinking level 3 with the creative category. While the subject with the field-dependent cognitive style does not meet the three indicators of creative thinking fluency, flexibility, and novelty, so the subject is at level 0 creative thinking with the uncreative category